Functional connectivity between the ventral anterior cingulate and amygdala during implicit emotional conflict regulation and daily-life emotion dysregulation. (30th July 2021) - Hua, Jessica P.Y.; Trull, Timothy J.; Merrill, Anne M.; Tidwell, Elise A.; Kerns, John G.
Abstract: Emotional conflict adaptation involving ventral anterior cingulate cortex (ACC) suppression of the amygdala is thought to be important in emotion regulation, with evidence of impaired implicit emotion regulation in emotional distress disorders. However, it is unclear how this impairment is associated with daily-life emotion dysregulation in emotional distress disorders. In the current study, female participants with an emotional distress disorder ( N = 27) were scanned with MRI while completing an implicit emotion conflict regulation task that involved identifying the facial expression of an image while ignoring an overlaid congruent or incongruent affect label. Participants then completed two weeks of ambulatory assessment of daily-life emotion dysregulation. Consistent with previous research on comorbid emotional distress disorders (Etkin and Schatzberg, 2011), there was no behavioral effect of emotional conflict adaptation ( p = .701) but a significant effect of congruent adaptation ( p = .006), suggesting impairment is specific to implicit emotional conflict regulation. Additionally, there was no neural evidence of emotional conflict adaptation in the ventral ACC and amygdala ( p s > .766). Further, in our primary psychophysiological interactions analyses, we examined ventral ACC-amygdala functional connectivity. As hypothesized, increased ventral ACC-amygdala functional connectivity for emotional conflict adaptation was associated with increased daily-life affective instability ( p = .022), but not mean daily-life negative affect ( p = .372). Overall, results provide behavioral and neural evidence of impaired implicit emotional conflict adaptation in individuals with emotional distress disorders and suggests that this impairment is related to daily-life affective instability in these disorders. Highlights: Examined implicit emotion regulation transdiagnostically in emotional disorders. Behaviorally found absence of implicit regulation of emotional conflict. Examined cingulate-amygdala connectivity during implicit emotion regulation. Found connectivity correlated with greater daily-life emotion affective instability. Impaired implicit emotion regulation might contribute to daily-life distress.